Observer la multimodalité en situations éducatives Circulations entre recherche et formation - Rivière, Véronique; Blanc, Nathalie (Éducation et savoirs en société, 2019)
Although the multimodal components of communication have been studied for some time in different scientific fields, and provide relevant frameworks for the analysis of social meaning, the organisation of interaction and knowledge sharing, this book looks at them in relation to the training of education professionals. It presents empirical studies in different educational contexts: special education; primary and secondary education; initial and continuing vocational training. Based on Gunther Kress's social semiotic theory, it examines the methodological conditions in which educational practice which mobilises a variety of semiotic resources - gestuality, gaze, space, proxemy, artefacts and language - can be observed and interpreted. But the authors also pose the question of how these observation and interpretation conditions can be reintroduced in the field of training for the education profession (How can we elicit the semiotic experiences of professionals in training? What can be observed? With what tools?) and call for the recognition of multimodal practices in the construction, mediation and acquisition of knowledge.